MINAT BELAJAR SISWA MENGGUNAKAN POCKET BOOK MATHEMATIC (POCKEMATH) BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN - R, Nurmala (Mathematics Education And Application Journal (META), 2021)
AbstractThe purpose of the study was to describe students' interest in learning in the use of Android-based Pocket Book Mathematical (Pockemath) media using smartphones as learning media in building materials. This research is a descriptive quantitative study with a sample of 30 students. Instrument used in the form of student learning interest questionnaires distributed to students before and after using Pocket Book Mathematics (Pockemath) media. The results of this study indicate that students experienced an increase in student interest in learning after using Android-based Pocket Book Mathematics (Pockemath) as a medium for learning mathematics for students. This can be seen from the comparison of students' interest in learning before using the media was 47.53 and after using the media it was 54.16. The increase in students' interest in learning is indicated by the gain value. The increase in student interest in learning obtained from data analysis is 0.56 and is in the medium categoryKeywords: Interest in Learning, Pocket Book, Android, Learning MediaAbstrakTujuan penelitian adalah mendeskripsikan minat belajar siswa dalam penggunaan media Pocket Book Mathematic (Pockemath) berbasis android dengan menggunakan smartphone Â sebagai media pembelajaran pada materi bangun ruang. Penelitian dilaksanakan dengan kuantitatif deskriptif melibatkan 30 siswa sebagai sampel Instrument penelitin adalah angket minat belajar siswa yang dibagikan ke siswa sebelum dan setelah menggunakan media Pocket Book Mathematic (Pockemath). Hasil penelitian ini mengalami peningkatan minat belajar siswa setelah menggunakan Pocket Book Mathematic (Pockemath) berbasis android sebagai media pembelajaran matematika untuk siswa. Hal ini dilihat dari perbandingan minat belajar siswa saat sebelum menggunakan media adalah sebesar 47,53 dan setelah menggunakan media media adalah 54,16. Peningkatan pada minat belajar siswa ditunjukkan dengan nilai gain. Peningkatan minat belajar siswa yang didapatkan dari analisis data adalah sebesar 0,56 dan berada pada kategori sedangÂ Kata Kunci: minat belajar, pocket book, android, media pembelajaran